Cross-Lagged Relationships Between Insomnia and Posttraumatic Stress Disorder in Treatment-Receiving Veterans. Issue 4 (July 2021) - Kartal, Dzenana; Arjmand, Hussain-Abdulah; Varker, Tracey; Cowlishaw, Sean; O'Donnell, Meaghan; Phelps, Andrea; Howard, Alexandra; Hopwood, Malcolm; McFarlane, Alexander; Bryant, Richard A.; Forbes, David; Cooper, John; et al.
Highlights: This study parsed the directionality of association between PTSD and insomnia over time. Results revealed a unique pattern of association during and following treatment. During the treatment period, PTSD symptoms significantly predicted insomnia symptoms. At 3 and 9 months posttreatment, insomnia symptoms persistently predicted PTSD symptoms. Abstract: Insomnia is a risk factor for the development of posttraumatic stress disorder (PTSD) while it is also plausible that PTSD symptoms can maintain insomnia symptoms. The present study examined longitudinal bidirectional relationships between insomnia and PTSD symptoms in treatment-seeking veterans. Participants were 693 ex-serving members of the Australian Defence Force who participated in an accredited, hospital-based outpatient PTSD program. Participants completed self-reported assessments of PTSD and insomnia symptoms at four time points: intake, discharge, 3-month, and 9-months posttreatment follow-up. Cross-lagged pathway analyses indicated significant bi-directional pathways between insomnia symptoms and PTSD symptoms at most time points. A final cross-lagged model between insomnia symptoms and the PTSD symptom clusters indicated that the PTSD symptom paths on insomnia symptoms, between intake and discharge, were attributable to reexperiencing PTSD symptoms. In contrast, across posttreatment follow-up time points there were significant paths of insomnia symptoms on all PTSD symptom clusters except from insomnia at 3-months to avoidance symptom at 9-months. PTSD symptoms and insomnia symptoms have bidirectional associations over time that may lead to the mutual maintenance or exacerbation of each condition following PTSD treatment. Where residual insomnia symptoms are present post-treatment, a sleep-focussed intervention is indicated and a sequenced approach to treatment recommended.